PERSEPSI SISWA TENTANG PROGRAM LITERASI POJOK BACA DALAM MENUMBUHKAN KARAKTER BERNALAR KRITIS DI SEKOLAH DASAR - Nabilah, Nabilah Alifia Rizki; Supriyadi Supriyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical reasoning in elementary school students in the era of fast and easily accessible information requires the ability to sort, identify, analyze, and make the right decisions. This fact requires a reading corner literacy program as an effort to foster critical reasoning characters. This study aims to analyze students' perceptions of the implementation of the reading corner program in fostering critical reasoning characters at SD Muhammadiyah 1 Gempol. The subjects of this study were 25 students. The research approach used qualitative with a phenomenological research type. Data collection used in-depth interviews, participant observation, documentation, and questionnaires. Data analysis in this study used interactive analysis techniques of the Miles and Huberman model with three interrelated and simultaneous activities until this study was completed, namely data coding, data presentation, and drawing conclusions. Data validity testing used triangulation of sources and methods. The findings of this study indicate that the reading corner literacy program in the corner of each class provides a variety of interesting and easily accessible reading materials as a means to bring books closer to students, foster a diligent attitude in learning, and interest in reading and foster critical reasoning characters through reading activities. The literacy corner program is felt by students to be able to grow critical reasoning characters with three indications. First, students' habit of reading in the reading corner in every corner of the classroom and being able to draw conclusions based on existing evidence. Second, being able to identify problems when explaining the material being read. Third, being able to analyze cause-and-effect relationships that show logical and analytical thinking as a strong foundation for critical reasoning characters.